Perceived value, satisfaction and visitor psychographics in community-based homestay tourism : behavioural intentions perspective / Salamiah A. Jamal - A. Jamal, Salamiah (2011)
Homestay is an alternative tourism product that has the potential to attract tourists due to a marked increase in international demand for tourism that allows tourists to observe, experience and learn about the way of life of the local residents of their destinations. Nevertheless, compared to other special interest tourism products, research on visitor behaviour in homestay tourism has been neglected. This study fills this void by investigating these remarkably distinctive tourism experiences through the concept of visitors' perceived value. Economists of tourism agree that valid and reliable measures of perceived value would allow for a comparison of value between tourism programmes. Such a comparison would enable tourism providers to identify which value dimensions are performing well. The purpose of this study was to test a model of visitors' perceived value of homestay tourism to explain the role of psychographics in behavioural intentions. At the theoretical level, this study aims to demonstrate that the conventional paradigm of perceived value, overall satisfaction and behavioural intentions is inadequate to explain visitors' behavioural intentions in the context of special interest tourism. A more realistic explanation is required that incorporates psychographic characteristics as a potentially influential variable.